2018
DOI: 10.1007/s10557-018-6812-z
|View full text |Cite
|
Sign up to set email alerts
|

Beta-Blockers and ACE Inhibitors Are Associated with Improved Survival Secondary to Ventricular Tachyarrhythmia

Abstract: ClinicalTrials.gov identifier: NCT02982473.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…In patients with systolic heart failure, ACEi/ARB therapy was already consistently shown to decrease both all-cause and cardiovascular mortality [18][19][20][21]. In line, we recently demonstrated that ACEi/ARB therapy is associated with improved long-term all-cause mortality in 528 propensity-matched patients presenting with an index episode of ventricular tachyarrhythmias on admission [14]. In contrast, statin therapy was not associated with allcause mortality in ES patients.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In patients with systolic heart failure, ACEi/ARB therapy was already consistently shown to decrease both all-cause and cardiovascular mortality [18][19][20][21]. In line, we recently demonstrated that ACEi/ARB therapy is associated with improved long-term all-cause mortality in 528 propensity-matched patients presenting with an index episode of ventricular tachyarrhythmias on admission [14]. In contrast, statin therapy was not associated with allcause mortality in ES patients.…”
Section: Discussionmentioning
confidence: 71%
“…Risk stratification was performed according to the following pharmacotherapies at discharge, as recently been described [14]: (1) ACEi/ARB was compared to non-ACEi/ARB patients. All types of ACEi or ARB were allowed.…”
Section: Definition Of Subgroupsmentioning
confidence: 99%
“…We identified 49 CA registries and 15 SCD registries, including the newly formed Australian UCDP Registry8–17 (table 1). Nine registries were categorised as ‘other’.…”
Section: Resultsmentioning
confidence: 99%
“…Cardiac autonomic nerves can induce or promote arrhythmias directly or indirectly by altering electrophysiological features [13,14]. A large retrospective study demonstrated that beta blockers and ACE inhibitors are associated with improved secondary survival in patients surviving ventricular arrhythmias on admission [15]. KCNH2 mediates the rapid activation of delayed rectifier potassium current (IKr), which is important for normal ventricular repolarization [16].…”
Section: Discussionmentioning
confidence: 99%